Balinese Arts And Culture As Tourism Commodity In Bali Tourism Promotion Videos - Desak Putu Eka Pratiwi; Putu Nur Ayomi; Komang Dian Puspita Candra (Mudra Jurnal Seni Budaya, 2017)
Tourism industry in Bali has increased significantly since 1970’s.  It is supported not only by its stunning nature of Bali but also its fascinating arts and culture. Bali has incredible arts, vibrant culture and unique traditions which have been very famous all over the world.  Many people especially foreigners want to see Balinese’s artistic artworks and experience their culture.   It motives them to travel to the island which also well known as the island of paradise.  Culture has a compelling role in tourism functioning as an internationally promoted commodity, a role that has often been the subject of disputes among academics. Some people consider that the changing of culture become tourist attractions will cause the loss of culture’s authenticity through modification.  Many scholars say that cultures that are performed as tourist attraction will lose its originality to adjust the tourist demand. This study aims at analyzing how Balinese arts and culture are packaged as tourism commodity in Bali tourism promotion videos which internationally published by Bali tourism board. The data were collected through observation method and note taking technique. The data were analyzed by using levels of product theory by Kotler and Armstrong (2008). The findings and discussions were presented through formal and informal methods. Our findings show that Bali tourism promotion videos consist of four dimensions: (1) essence of product, (2) real product, (3) processed real product and (4) additional product, as described in the discussion.Industri pariwisata di Bali terus meningkat sejak tahun 1970. Hal ini didukung tidak hanya oleh keindahan alam pulau Bali tetapi juga seni dan budaya Bali yang begitu memukau. Bali memiliki kekayaan seni yang menakjubkan, budaya yang dinamis dan berbagai tradisi unik yang begitu terkenal di seluruh dunia. Banyak orang, khusunya orang asing, yang ingin melihat karya seni Bali yang artistik dan mengalami sendiri budaya masyarakat Bali. Hal tersebut mendorong mereka untuk berwisata ke pulau Bali yang juga dikenal sebagai pulau surga. Budaya memiliki memiliki peran yang kuat dalam dunia pariwisata yang berfungsi sebagai alat promosi secara internasional, sebuah peran yang sering menjadi bahan perdebatan para ahli. Beberapa ahli berpikir bahwa dengan berubahnya fungsi budaya sebagai atraksi wisata dapat mengakibatkan hilangnya keaslian atau originalitasnya karena mengalami modifikasi untuk menyesuaikan dengan kebutuhan wisatawan. Penelitian ini bertujuan untuk menganalisis bagaimana seni dan budaya Bali dikemas sebagai komoditas pariwisata dalam video promosi pariwisata Bali yang telah dipublikasikan secara internasional oleh Dinas Pariwisata Bali. Data dikumpulkan dengan metode observasi dan kemudian dianalisis menggunakan teori dari Kotler and Armstrong (2008). Temuan dan pembahasan dipaparkan dengan metode formal dan informal. Seara umum temuan kami menunjukkan bahwa video pariwisata Bali terdiri dari empat dimensi, yaitu: (1) essence of product, (2) real product, (3) processed real product and (4) additional product, yang dijelaskan dalam sub bab pembahasan.